THE EFFECTS OF ADSORBENT MATERIALS ON THE LIPID QUALITY OF LEMURU FISH OIL AND THE ENRICHMENT OF OMEGA-3 USING LIPASE - Raden Tina Rosmalina; Wawan Kosasih; Sri Priatni (Jurnal Teknologi dan Industri Pangan, 2021)
Sardinella (lemuru) is a genus of fish that is widespread in the East Java Sea region, especially in Muncar, Banyuwangi in East Java Province, Indonesia. Marine fishes are rich in essential fatty acids, including omega-3. This study aims to improve the quality of lemuru fish oil through the use of adsorbent materials such as bentonite and activated carbon. The sample was analyzed to determine its free fatty acid (FFA) content and peroxide value (PV) using the titrimetric method. The clarity of the oil was determined using the spectrophotometric method (λ 440 nm). The omega 3 content from the fish oil sample was then enriched through enzymatic reactions using lipase. Enzymatic reactions were carried out for 5, 10, 15, 20, 35, and 47 hours with a lipase concentration of 500, 1000, 1500, and 2000 units respectively. The omega-3 content of the fish oil products was analyzed using the GC-FID method. The results show that the addition of 3% activated carbon and bentonite in the fish oil reduced the FFA and PV results. Moreover, the absorbance value at λ 440 nm was also reduced from 0.883 to 0.559. The highest content of omega-3 was obtained through hydrolysis with lipase at a concentration of 1000 units for 35 hours with alpha-methyl linolenate (ALA), methyl all-cis-5,8,11,14,17-eicosapentanoate (EPA) and cis-4,7,10,13,16,19-docosa-hexaenoic acid methyl ester (DHA) at 0.78, 1.06, and 0.29% respectively.